Análisis de estados financieros mediante razones de solvencia y rentabilidad en empresas pymes manufactureras de Machala, período 2023. - Rosario Ordoñez, Jose Rodolfo; Viera Seminario, Allison Claribel (Machala : Universidad Técnica de Machala, 2025)
Manufacturing SMEs in Machala face serious challenges in sustaining their economic growth due to limited financial management and a lack of knowledge in using analytical tools to assess their debt capacity and profitability. This compromises their sustainability and restricts access to financing, thereby affecting their competitiveness in the local market. The objective of this study is to analyze the financial statements of manufacturing SMEs in the canton of Machala by applying solvency and profitability financial tools to assess their financial health, compliance with obligations, and support strategic financial decision-making. To this end, a quantitative approach was adopted, under the positivist paradigm and a non-experimental, descriptive design. The analytical method and observation technique were used, applying a structured guide to the financial statements of 16 active manufacturing SMEs in Machala in 2023, with data obtained from the Superintendence of Companies.The results revealed high levels of indebtedness in most companies, with critical leverage and equity debt ratios, reflecting a strong dependence on external financing. Consequently, very few companies showed positive profitability indicators, highlighting efficient resource management. In this regard, it is concluded that weak financial structures, limited accounting culture, and low self-financing capacity are key factors hindering the development of these organizations, Therefore, it is necessary for these companies to strengthen their financial capabilities to improve their sustainability and competitiveness.
Las empresas pymes manufactureras de Machala enfrentan serias dificultades para sostener su crecimiento económico, debido a una limitada gestión financiera y al desconocimiento en el uso de herramientas analíticas que permitan evaluar su capacidad de endeudamiento y rentabilidad. Esto compromete su sostenibilidad y limita su acceso a financiamiento, afectando su competitividad en el mercado local. El objetivo de este trabajo fue analizar los estados financieros de las empresas pymes manufactureras del catón Machala, aplicando las herramientas financieras de solvencia y rentabilidad, para conocer la salud financiera de las empresas, el cumplimiento de sus obligaciones, y la toma de decisiones estratégicas en la gestión financiera. Para esto, se adoptó un enfoque cuantitativo, bajo el paradigma positivista y un diseño no experimental de tipo descriptivo, usando el método analítico y la técnica de observación, aplicando una guía estructurada sobre los estados financieros de 16 empresas PYMES manufactureras activas en Machala, en 2023, cuyos datos fueron extraídos del portal de la Superintendencia de Compañías. Los resultados evidenciaron altos niveles de endeudamiento en la mayoría de las empresas, con ratios de apalancamiento y endeudamiento patrimonial críticos, reflejando una fuerte dependencia del financiamiento externo. En consecuencia, muy pocas empresas mostraron indicadores positivos de rentabilidad, destacando una gestión eficiente de sus recursos. En este sentido, se concluye que la débil estructura financiera, la escasa cultura contable y la limitada capacidad de autofinanciamiento son factores determinantes que obstaculizan el desarrollo de estas organizaciones. Por tanto, es necesario que estas empresas fortalezcan sus capacidades financieras para mejorar su sostenibilidad y competitividad.
Keywords: ESTADOS FINANCIEROS; EMPRESAS PYMES; RAZONES FINANCIERAS; SOLVENCIA